THE PRINCIPLE OF JUSTICE IN NEW UZBEKISTAN - Muzaffar Ziyodullaevich, Ziyodullaev (Antis Publisher, 2024)
The principle of a fair trial is a cornerstone of Uzbekistan’s Constitution and legal framework, aimed at safeguarding citizens' rights and freedoms, as well as the interests of individuals, society, and the state. Significant reforms have been implemented to ensure judicial independence, equality before the law, and the presumption of innocence. Measures such as the establishment of the Supreme Council of Judges, the integration of information and communication technologies into court processes, and the digitization of judicial activities have enhanced transparency, efficiency, and accessibility in the justice system. Presidential decrees, including PD-4850 (2016) and PD-6034 (2020), introduced structural improvements, streamlined judicial procedures, and enhanced the professionalism and accountability of judges. The adoption of the Updated Constitution in 2023 further strengthened judicial guarantees, emphasizing the independence of the judiciary, open trials, and proportionality in legal measures. These reforms have yielded tangible outcomes: thousands of unjust charges were dismissed, over 1,200 individuals were acquitted, and significant advancements were made in resolving legal disputes fairly and efficiently. By embedding international standards and modern practices, Uzbekistan’s judicial system continues to evolve, ensuring robust legal protections and fostering public trust in justice.